Comparative evaluation of linear and curvilinear ultrasound transducers for confirmation of endotracheal tube placement in emergency intubation - Dinesh, Dipin; Suseel, Appu; Chathappan, Rajeev Punchalil; Palatty, Babu Urumese (International Journal of Research in Medical Sciences, 2026)
Background: Accurate and rapid confirmation of endotracheal tube (ETT) placement is critical in emergency airway management, as unrecognized oesophageal intubation can lead to catastrophic outcomes. Although waveform capnography is considered the gold standard, it has limitations in low pulmonary flow states. Point-of-care ultrasonography has emerged as a useful adjunct, but the optimal choice of ultrasound transducer for ETT confirmation remains unclear. This study aimed to compare the speed and reliability of linear and curvilinear ultrasound transducers for confirming ETT placement in emergency intubation. Methods: A hospital-based non-randomized controlled trial was conducted over 18 months (January 2020 to June 2021) in the Emergency Department of a tertiary care centre in South India. Adult patients (≥18 years) undergoing emergency endotracheal intubation were included, while those in cardiac arrest with ongoing CPR or requiring surgical airways were excluded. Participants were allocated to linear or curvilinear transducer groups using the serial-numbered opaque sealed envelope technique. The primary outcomes were time to exclusion of oesophageal intubation and time to confirmation of left lung sliding, while secondary outcomes included total procedure time up to five-point auscultation and operator confidence. Results: Eighty-seven patients were analyzed (46 linear, 41 curvilinear). Baseline characteristics were comparable between groups. The linear transducer demonstrated significantly shorter times for exclusion of oesophageal intubation, confirmation of left lung sliding, and total procedure time (p<0.0001 for all). Operator confidence was significantly higher with the linear transducer. Procedural times showed no association with age or indication for intubation, though shorter times were observed in male patients. Conclusions: Linear ultrasound transducers provide faster and more reliable confirmation of ETT placement with higher operator confidence compared to curvilinear transducers, supporting their preferential use in emergency airway management.